Intraoperative Ultrasound in Spine Decompression Surgery: A Systematic Review. Issue 2 (15th January 2022) - Tat, Jimmy; Tat, Jessica; Yoon, Samuel; Yee, Albert J.M.; Larouche, Jeremie
Abstract : Study Design: Systematic review. Objective: The aim of this study was to review the current spine surgery literature to establish a definition for adequate spine decompression using intraoperative ultrasound (IOUS) imaging. Summary of Background Data: IOUS remains one of the few imaging modalities that allows spine surgeons to continuously monitor the spinal cord in real-time, while also allowing visualization of surrounding soft tissue anatomy during an operation. Although this has valuable applications for decompression surgery in spinal canal stenosis, it remains unclear how to best characterize adequacy of spinal decompression using IOUS. Methods: We conducted a systematic search of multiple databases including: Medline, Embase, and Cochrane Central Register of Controlled Trials Strategy. Our search terms were spine, spinal cord diseases, decompression surgery, ultrasonogra-phy, and intraoperative period. We were interested in studies that used intraoperative use of ultrasound imaging in spinal decompression surgery for the cervical, thoracic, and lumbar spine. Study quality was evaluated using the Methodological Index for Non-Randomized Studies (MINORS). Results: Our search strategy yielded 985 of potentially relevant publications, 776 underwent title and abstract screening, and 31 full-text articles were reviewed. We found IOUS to be useful in spine surgery for decompression of degenerative cases in all regions of the spine. The thoracic spine was unique for IOUS-guided decompression of fractures, and the lumbar spine for decompressing nerve roots. Although we did not identify a universal definition for adequate decompression, there was common description of decompression that qualitatively described the ventral aspect of the spinal cord being "free floating" within the cerebrospinal fluid. Other measurable definitions, such as spinal cord diameter or spinal cord pulsatility, were not good definitions given there was insufficient evidence and/or poor reliability. Conclusion: The systematic review examines the current literature on IOUS and spinal decompression surgery. We identified a common qualitative definition for adequate decompression involving a "free floating" spinal cord within the cerebrospinal fluid which indicates that the spinal cord is free from contact of the anterior elements. Level of Evidence: 1 Abstract : The systematic review examines the current literature on IOUS and spinal decompression surgery. We identified a common qualitative definition for adequate decompression involving a "free floating" spinal cord within the cerebrospinal fluid which indicates that the spinal cord is free from contact of the anterior elements.